2019
DOI: 10.21769/bioprotoc.3149
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Yeast Cell Survival Following Hydrogen Peroxide Exposure

Abstract: In the presence of oxidative stress, cellular defense systems that can detoxify reactive oxygen species are activated through multiple signaling cascades and transcriptional reprogramming. The budding yeast Saccharomyces cerevisiae has served as an excellent model for genetically-identifying factors important for the response to oxidative stress. Here, we describe two assays for testing yeast gene deletion strains or strains overexpressing a gene of interest for viability following oxidative stress induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…We first tested our growth conditions for wildtype cells grown in aerobic and hypoxic conditions. We observed that we obtained the most consistent results by diluting stationary phase cultures to very low OD 600 and allowing them to grow to OD 600 ∼0.4-0.8 over the course of 18 hours in hypoxia, similar to how we tested set4Δ mutants sensitivity to oxidative stress (10,12). Under these conditions, the PAU genes were highly upregulated, and there was also significant upregulation of YGL262W , although expression of COS12 and YPS5 at TEL07L remained mostly unchanged in hypoxic compared to aerobic growth ( Figure 2A ).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…We first tested our growth conditions for wildtype cells grown in aerobic and hypoxic conditions. We observed that we obtained the most consistent results by diluting stationary phase cultures to very low OD 600 and allowing them to grow to OD 600 ∼0.4-0.8 over the course of 18 hours in hypoxia, similar to how we tested set4Δ mutants sensitivity to oxidative stress (10,12). Under these conditions, the PAU genes were highly upregulated, and there was also significant upregulation of YGL262W , although expression of COS12 and YPS5 at TEL07L remained mostly unchanged in hypoxic compared to aerobic growth ( Figure 2A ).…”
Section: Resultssupporting
confidence: 65%
“…For hypoxic growth, the culture flasks were placed in BD GasPak EZ anaerobe pouch system and incubated at 30°C. For hydrogen peroxide-treated cultures, cells were grown to mid-log phase (OD 600 ∼0.6-0.8) and then treated with 0.4mM H 2 O 2 for 30 min (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A drop (5 µl) of each culture was applied on YPD plates and incubated at 30°C (unstressed), 37°C (HTS) and 15°C (low-temperature stress; Mishra et al, 2018). In a separate set of experiments, the cultures were grown on YPD plates independently supplemented with 0.5 M NaCl (hypersalinity; Piao et al, 1999) and 1.2 M sorbitol (osmotic stress; Zhi et al, 2013), and incubated at 30°C for 36 h. For oxidative stress, overnight-grown YPD culture was supplemented with 4 mM H 2 O 2 for 30 min, and similar parameters were followed for spotting on YPD plates (Tran and Green, 2019).…”
Section: Expression Of Ta2cp In Heterologous Systemsmentioning
confidence: 99%
“…The impact of UV-C-induced oxidative stress on DBY746 yeast was examined to test this hypothesis using our published protocol [6,23,26]. The resulting yeast survival, estimated with a quantitative colony counting assay [49], and ROS/RNS production are presented in Figure 4. Under these oxidative conditions induced by UV-C, AE and CHL supplementations significantly improved the survival of yeast (Figure 4a) in conjunction with their ability to Peer-reviewed version available at Life 2020, 10, 80; doi:10.3390/life10060080 significantly reduce ROS / RNS production (Figure 4b).…”
Section: Almond Skin Extract and Chlorogenic Acid Increased Yeast Surmentioning
confidence: 99%